1992
DOI: 10.1002/jcc.540130716
|View full text |Cite
|
Sign up to set email alerts
|

Electronegativity and Bader's bond critical point

Abstract: The electronegativities (xp) of some 36 atoms/groups (including some 6 ionic ones) X are calculated from the atomic charges in the corresponding methyl species CHBX that were obtained by applying Bader's theory of atoms in molecules. The numerical values of the XI for the various groups studied are reasonable and correlate linearly with the two existing experimental scales for group electronegativity, Inamoto's i scale and the 'JCC (ortho-ipso) coupling constants in the monosubstituted benzenes, to satisfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…The computed Fe‐(b.c.p. Fe‐M ) distances are 1.178 Å for 1 and 1.167 Å for 3 , while a meaningfully shorter distance was found for the Au derivative 5 (1.136 Å) . On the same basis, it might also be concluded that Fe‐Au bonds are stronger than Fe–Cu and Fe–Ag bonds, in agreement with the greater stability of 5 and 6 compared to 1 – 4 .…”
Section: Resultsmentioning
confidence: 63%
“…The computed Fe‐(b.c.p. Fe‐M ) distances are 1.178 Å for 1 and 1.167 Å for 3 , while a meaningfully shorter distance was found for the Au derivative 5 (1.136 Å) . On the same basis, it might also be concluded that Fe‐Au bonds are stronger than Fe–Cu and Fe–Ag bonds, in agreement with the greater stability of 5 and 6 compared to 1 – 4 .…”
Section: Resultsmentioning
confidence: 63%
“…A bond critical point (BCP) of the type (À3, 1) is located in the Cu-S bond. In Bader's theory, presence of a BCP ensures chemical bonding [27]. The electron density q at the BCP is 0.02 e Å À3 .…”
Section: Resultsmentioning
confidence: 99%
“…32 Conforme as trajetórias do gradiente da densidade eletrônica se moldam para descrever um sistema químico, estas trajetórias não se originam do infinito, mas de um ponto localizado entre dois atratores, os chamados Pontos Críticos de Ligação (BCPBond Critical Point). 33 A identificação dos BCP foi apresentada como uma proposta evolutiva aos conceitos da população de recobrimento equivalente de Mulliken, 34 a qual foi usada durante muito tempo em estudos de ligações químicas e interações intermoleculares. 35 Quando duas trajetórias de ∇r direcionadas aos núcleos são formadas a partir de um único BCP, estas são chamadas de Linhas Interatômicas (ILInteratomic Lines) 36 ou Trajetórias de Ligação (BP -Bond Path).…”
Section: Em 1939 Pauling Editou O Clássico Livro Texto "Nature Of Theunclassified